A REVIEW:THERAPEUTIC POTENTIAL OF AUTOPHAGY IN GASTRIC CANCER (The Research of Medical Science Review, 2025)
A natural and cellular process in human that comprises breaking down and eliminating old, spoiled, or irregular proteins and other ingredients in the cytoplasm. Derivatives of this breakdown recycled specially during starvation by a complex mechanism named as autophagy. During nutrient deprived condition autophagy performs bipolar role in case of cancer. In gastric cancer (GC) autophagy related protein (ATG) is crucial for diagnostic and treatment of GC in early and later stage. Aim and significance of this review is to elaborate the role of ATG and pre-clinical and clinical results by using in amalgamation with existing drugs for the therapy of GC.